THE CORRELATION BETWEEN READING HABITS AND STUDENTS’ VOCABULARY MASTERY AT ENGLISH EDUCATION DEPARTMENT UNIVERSITAS MUHAMMADIYAH YOGYAKARTA - Eva Aflakha Naimatun (PBI 15 UMY 021, 2015)
*21 This research aims to identify the students’ reading habit, to reveal students’ vocabulary mastery and to find out the correlation between reading habit and vocabulary mastery. This research was conducted in English Education Department Department (EED of Universitas Muhammadiyah Yogyakarta (UMY). The population of EED UMY batch 2013 was 194, moreover the researcher used convenience sample. 106 students of EED UMY batch 2013 participated in this research. This research used quantitative approach and correlation as the methodology. Moreover, this research used two instruments namely questionnaire and vocabulary test. The research found out that the EED UMY students’ batch 2013 had good reading habit. It was supported by the students reading habits mean value of 3.09. The research also found out that the vocabulary mastery of EED UMY was in good category since the mean value of vocabulary was 3.54. The last result showed that the correlation between EED UMY students’ reading habit and vocabulary mastery is in very weak criteria of correlation. It means that the correlation was positive but not significant with the correlation value was 0.106 and the probability value wasm0.278